Pengaruh Kepuasan Komunikasi Organisasi Terhadap Kinerja Karyawan : Tinjauan Literatur - Cecilia Raisadina Maharani (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
To be able to achieve success and common goals, it is necessary to have a satisfaction of communication. Employees or members of the organization are important assets in achieving organizational goals. Therefore there is a need for awareness to advance the quality of performance in order to achieve common goals. This study aims to determine the effect of organizational communication satisfaction on employee performance. The research was conducted by library research. Sources of research data were obtained from books, articles and journal publications which were collected using documentation techniques. The results of the study show that it is related to employee performance. It is better if members of the organization improve the quality of communication first, because when an employee is satisfied with communication in an organization, it will improve his performance.